2015
DOI: 10.1007/s10344-015-0931-7
|View full text |Cite
|
Sign up to set email alerts
|

Diverse gammacoronaviruses detected in wild birds from Madagascar

Abstract: To date, infectious bronchitis virus (IBV) is potentially found in wild birds of different species. This work reports the survey of coronaviruses in wild birds from Madagascar based on the targeting of a conserved genome sequence among different groups of CoVs. Phyl o g e n e t i c a n a l y s e s r e v e a l e d t h e p r e s e n c e o f gammacoronaviruses in different species of Gruiformes, Passeriformes, Ciconiiformes, Anseriformes, and Charadriiformes. Furthermore, some sequences were related to various IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 16 publications
2
29
1
Order By: Relevance
“…Even within the Charadriiformes lineages, the degree of genetic difference to duck sequences was much less than that seen in the deltacoronavirus phylogeny. The phylogeny based on the amino acid sequence of the gammacoronaviruses separated the majority of the duck and Charadriiform gammacoronaviruses into separate branches, however both the curlew sandpiper gammacoronaviruses and a single ruddy turnstone gamma-CoV were identical in amino acid homology to duck Australian duck gamma-CoV's as well as duck gamma-CoV's identified in other investigations 16,18,20,25,27 . These results again suggest that migratory Charadriiformes may share gammacoronaviruses with other avian species 16,18 and are therefore important vectors and reservoir of coronaviruses.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Even within the Charadriiformes lineages, the degree of genetic difference to duck sequences was much less than that seen in the deltacoronavirus phylogeny. The phylogeny based on the amino acid sequence of the gammacoronaviruses separated the majority of the duck and Charadriiform gammacoronaviruses into separate branches, however both the curlew sandpiper gammacoronaviruses and a single ruddy turnstone gamma-CoV were identical in amino acid homology to duck Australian duck gamma-CoV's as well as duck gamma-CoV's identified in other investigations 16,18,20,25,27 . These results again suggest that migratory Charadriiformes may share gammacoronaviruses with other avian species 16,18 and are therefore important vectors and reservoir of coronaviruses.…”
Section: Discussionmentioning
confidence: 78%
“…The phylogeny based on the amino acid sequence of the gammacoronaviruses separated the majority of the duck and Charadriiform gammacoronaviruses into separate branches, however both the curlew sandpiper gammacoronaviruses and a single ruddy turnstone gamma-CoV were identical in amino acid homology to duck Australian duck gamma-CoV's as well as duck gamma-CoV's identified in other investigations 16,18,20,25,27 . These results again suggest that migratory Charadriiformes may share gammacoronaviruses with other avian species 16,18 and are therefore important vectors and reservoir of coronaviruses. Hughes, et al 23 and Chu, et al 16 identified similar gammacoronavirus sequences between Charadriiformes and Anseriformes, while Lima, et al 18 found similar gammacoronaviruses in Charadriiformes and Gruiformes in Madagascar.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations